Electrochemical deposition of bimetallic sulfides on novel BDD electrode for bifunctional alkaline seawater electrolysis - Mingxu Li; Genjie Chu; Jiyun Gao; Xiaolei Ye; Ming Hou; Shenghui Guo; Yunchuan Li; Ziqi Zhou; Li Yang; Pascal Briois (Scientific Reports)
Abstract Seawater electrolysis is an ideal technology for obtaining clean energy—green hydrogen. Developing efficient bifunctional catalysts is crucial for hydrogen production through direct seawater electrolysis. Currently, metal substrates loaded with active catalysts are widely employed as electrodes for seawater electrolysis. However, the challenge of metal corrosion cannot be ignored. In this work, the boron-doped diamond (BDD) with excellent corrosion resistance was explored as a substrate for loading active catalysts in seawater electrolysis. A step-by-step electrodeposition method was used to fabricate the FeCoS/Ni/BDD electrode, effectively addressing the poor adhesion of the FeCoS active layer to the BDD substrate. The resulting electrode demonstrated interesting bifunctional catalytic performance, achieving oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) overpotentials of 425 mV and 360 mV, respectively, in alkaline simulated seawater (1 M KOH and 3.5 wt% NaCl) at a current density of 100 mA cm− 2. Furthermore, by increasing the KOH concentration in the alkaline simulated seawater to 3 M, the OER and HER overpotentials of the electrode significantly decreased to 383 and 300 mV, respectively. This work offers a novel approach for utilizing BDD substrates in the design of corrosion-resistant electrodes for alkaline seawater electrolysis.